1,000 low-calorie recipes - Newgent, Jackie (Wiley, 2012)
"Chapters include Small Plates, Finger Foods, and Snacks; Meat Entrees; Pizzas, Pizettes and Savory Pies; Desserts, Quick Breads and Muffins; and Spirits and Other Alcoholic Beverages"--